Myocardial Function in Offspring Aged 5 to 8 Years of Pregnancy Complicated by Severe Preeclampsia Measured by Two-Dimensional Speckle-Tracking Echocardiography - Chen, Huiyun; Gong, Yu; Sun, Fangcan; Han, Bing; Zhou, Bingyuan; Fan, Jiali; Gu, Xinxian (Frontiers in Physiology, 2022)
Objective: Quantitative assessment of myocardial strain in preterm children aged 5 to 8 years of pregnancy complicated by severe preeclampsia by two-dimensional speckle tracking echocardiography. Method: A cohort study of 23 preterm children delivered by severe PE pregnant women from 2010 to 2012 in the First Affiliated Hospital of Soochow University was carried out. 23 preterm children from uneventful pregnancies in the same period served as controls. Myocardial functions including left ventricular longitudinal strain, radial strain, circumferential strain and right ventricular longitudinal strain were evaluated by conventional Doppler, tissue Doppler imaging and two-dimensional speckle-tracking echocardiography (2D STE). All examinations were performed by an experienced ultrasonographist using the VIVID E9 (GE Healthcare) machine, according to standard techniques. Results: Children aged 5-8 years delivered from severe PE presented less weight (24.41 vs 20.89 kg, P<0.05), shorter height (124.1 vs 115.6 cm, P<0.05) and faster heart rates (84 vs 93 bpm, P<0.05) compared to offspring of normotensive women. There were no significant differences in global left ventricular longitudinal strain, radial strain, circumferential strain and right ventricular longitudinal strain between the children in the experimental group and the control group (P>0.05). Conclusion: Exposure to the intrauterine environment of severe PE during the fetal period did not have a significant impact on cardiac structure in premature children at 5-8 years old, but they had a higher resting heart rate which may be associated with cardiovascular disease in the long run.